عہد نبوی وفاروقی میں آفات، وباؤں کے دوران کفالت عامہ کا تصور اور حکمت عملی ، عصری تناظر میں ایک تحقیقی جائزہ: A research Study on the Concept of Public Welfare and Strategy during Natural Disasters and Epidemics in the Prophetic and Farooqi Era in contemporary context. - Rafiudin; Dr.Syed Ghszanfer Ahmad (MEI, 2025)
A disaster is an extraordinary natural event that disrupts the normal course of life, while an epidemic is a deadly contagious disease that spreads rapidly and affects a large number of people. Both have scientific as well as spiritual causes that lead to their occurrence. Disasters and epidemics have profound human, economic, environmental, and moral impacts, affecting not only individuals but entire social systems and governance structures.The purpose of this research is to review the public welfare measures, strategies, and models implemented during the Prophetic era and the Caliphate of Umar in times of such crises. In both periods, the state ensured the welfare of the people not only through spiritual means but also through practical, social, and economic actions.This study adopts an analytical approach to evaluate the policies of these eras in the context of contemporary challenges. The Islamic welfare state is not merely a theoretical concept but a model based on practical governance and responsibility, where the state is fully accountable for the welfare of its people. If current governments and institutions adopt the strategies of the Prophetic and Umar’ eras, not only can they effectively confront present disasters and epidemics, but they can also establish a just, ethical, and stable society.